2014
DOI: 10.1007/s11695-014-1421-9
|View full text |Cite
|
Sign up to set email alerts
|

Laparoscopic Sleeve Gastrectomy is Safe and Effective in Elderly Patients: A Comparative Analysis

Abstract: SG is safe and effective in patients ≥62 years. Weight loss and the beneficial effects on comorbidities are equivalent among elderly and younger patients. SG should be offered to elderly patients who are deemed to be appropriate candidates.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0
4

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(21 citation statements)
references
References 28 publications
0
17
0
4
Order By: Relevance
“…Age groups under and over 62 years maintained a >20 % total body weight loss and a change in BMI>10 during the 3-year follow-up period [36]. Another recent study comparing the patients over 60 years with those under 50 years for up to 22 months after LSG showed better results in the younger age group for %EBMIL.…”
Section: Discussionmentioning
confidence: 91%
“…Age groups under and over 62 years maintained a >20 % total body weight loss and a change in BMI>10 during the 3-year follow-up period [36]. Another recent study comparing the patients over 60 years with those under 50 years for up to 22 months after LSG showed better results in the younger age group for %EBMIL.…”
Section: Discussionmentioning
confidence: 91%
“…Of the 28 studies in which weight outcomes for older and younger persons were compared, 16 found no significant difference in weight loss between groups, and seven studies reported less weight loss in older than younger participants . Greater total weight loss in younger participants but no difference in percent excess weight loss (%EWL) between groups was reported in two studies .…”
Section: Resultsmentioning
confidence: 99%
“…Ten studies evaluated only the safety of bariatric surgery, and the remainder evaluated weight loss efficacy as well as safety, although the reported measures of efficacy and safety varied between studies. Thirty‐nine of the 66 included studies compared outcomes between older adults and a younger group, and in 12 of these studies, groups were matched for characteristics such as sex, BMI, and surgery type. The remaining studies reported results for older persons without a comparison group.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The prevalence of surgical operations was 478 patients receiving laparoscopic adjustable gastric banding (LAGB) [14][15][16][17][18][19]24], 52 laparoscopic sleeve gastrectomies (LSGs) [20,21], 36 Roux-en-Y gastric bypasses [15,23] and a mixed series of open and laparoscopic gastric bypass (LGBP) operations in 80 patients [22]. No consistent definition of improvement nor resolution of T2DM, hypertension or OSA was used in these studies.…”
Section: Outcomes Of Bariatric Surgerymentioning
confidence: 99%